2021
DOI: 10.1186/s12893-021-01221-3
|View full text |Cite
|
Sign up to set email alerts
|

Trunk fat volume can be a predictor of postoperative complications after gastrectomy: a retrospective cohort study

Abstract: Background Obesity can affect postoperative outcomes of gastrectomy. Visceral fat area is superior to body mass index in predicting postoperative complications. However, visceral fat area measurement is time-consuming and is not optimum for clinical use. Meanwhile, trunk fat volume (TFV) can be easily measured via bioelectrical impedance analysis. Hence, the current study aimed to determine the ability of TFV to predict the occurrence of complications after gastrectomy. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…However, there have been no studies on other indicators of short-term outcomes and operative time using the BIA device, except for skeletal muscle mass, in patients who had undergone colorectal surgery. Shiomi et al [ 39 ] reported that trunk fat volume measured by using a BIA device can be a useful parameter for the evaluation of obesity and a predictor of complications after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been no studies on other indicators of short-term outcomes and operative time using the BIA device, except for skeletal muscle mass, in patients who had undergone colorectal surgery. Shiomi et al [ 39 ] reported that trunk fat volume measured by using a BIA device can be a useful parameter for the evaluation of obesity and a predictor of complications after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…BIA is widely used as it is a simple and non-invasive method that provides accurate results [19,20]. Several reports have evaluated postoperative changes in body composition using BIA and analyzed the risk factors for postoperative complications in patients with gastric cancer [21][22][23]. Moreover, in patients with colorectal cancer, a preoperative low SMI based on the BIA method was considered a risk factor for postoperative ileus [24], and preoperative visceral fat area measured by BIA was an independent prognostic factor for disease-free survival [25].…”
Section: Discussionmentioning
confidence: 99%
“…1416 Regarding direct surgical factors, previous literature has demonstrated increased visceral fat volume associated with predisposition to multiple cancers, prolonged hospital stay, and increased risk of hospital mortality. 1719 The mechanism by which increasing visceral fat results in an increased risk for infection, seroma, and epidermolysis is unclear but may be secondary to compromised vascular endothelial function and angiogenesis. 20…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Regarding direct surgical factors, previous literature has demonstrated increased visceral fat volume associated with predisposition to multiple cancers, prolonged hospital stay, and increased risk of hospital mortality. [17][18][19] The mechanism by which increasing visceral fat results in an increased risk for infection, seroma, and epidermolysis is unclear but may be secondary to compromised vascular endothelial function and angiogenesis. 20 Prior studies evaluating the impact of preoperative CTA abdominal visceral adipose distribution on donor site complications in patients undergoing abdominally based autologous reconstruction have demonstrated inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%